Negocios Internacionales en la nueva normalidad - Oyarse Cruz, Javier Gustavo (2021)
Throughout this article, the author intends to analyze whether Peru is prepared to continue with international business in the new normalcy caused by the new coronavirus. It also shows that the digitization of custom services has been achieved, both in the public and private sectors, so that more virtual tools exist.